Social support and mental health: the mediating role of perceived stress - Acoba, Evelyn F. (Frontiers in Psychology, 2024)
Social support has been associated with improved mental health; however, the mechanisms underlying this relationship remain unclear. This study aimed to explore whether perceived stress mediate the relationship between social support and positive affect, anxiety, and depression. Drawing from Lazarus and Folkman's stress and coping theory, the study emphasized the influential role of social support in appraising stressful events. A cross-sectional survey was conducted online among 426 Filipino adults during the peak of the COVID-19 pandemic. Participants completed measures including the Multidimensional Scale of Perceived Social Support (MSPSS), the Perceived Stress Scale-10 (PSS-10), the Positive Affect subscale of PANAS, and the Depression and Anxiety subscales of DASS-21. The hypotheses of the study were tested using mediation analysis. Consistent with the hypotheses, perceived stress significantly mediated the relationship between family and significant other support with positive affect, anxiety, and depression. Family and significant other support decreased perceived stress, increasing positive affect, and decreasing anxiety and depression. On the other hand, perceived stress did not mediate the relationship between friend support and positive affect, anxiety, and depression. Implications and future research directions are discussed.